Enhancing geoeconomic resilience by applying biomimetic principles in urban agriculture - Toth, Mihaly Alex (Nanyang Technological University, 2023)
The dissertation intends to approach the application of biomimetic principles as a framework in urban agriculture to further enhance local and national food security. Biomimicry is still in an infant phase in social sciences, and by identifying analogies in natural ecosystems or by re-exploring nature-inspired traditional ecological knowledge, food security system could be improved to be able to mitigate potential consequences of geoeconomic measures, logistic disruptions or natural disasters. Since nature functions in a completely sustainable manner, why wouldn’t humans follow nature's patterns which have been perfected for billions of years? The ability of urban agriculture to act as an additional food security mechanism during food embargoes is in the particular focus of this paper. The research touches upon characteristics of previous food embargoes, along with political consequences of food shortages. The current methods how states and, especially, cities tend to prepare for food supply issues are discussed, meanwhile untapped potential of urban food production is also highlighted. In the second half of the dissertation, biomimicry and its principles are examined with their infrequent application in urban areas at the present. As permaculture represents the most nature-inspired cultivation